2015
DOI: 10.1007/s00296-015-3308-z
|View full text |Cite
|
Sign up to set email alerts
|

CCR5Δ32 (rs333) polymorphism is associated with the susceptibility to systemic lupus erythematosus in female Brazilian patients

Abstract: The role of CCR5Δ32 (rs333) polymorphism in the pathogenesis of systemic lupus erythematosus (SLE) has been evaluated worldwide. The aim of this study was to determine the association between CCR5Δ32 polymorphism with the susceptibility to SLE and the activity of disease in female Southern Brazilian patients. The study enrolled 169 female SLE patients and 132 unrelated female healthy individuals. Baseline clinical, laboratorial characteristics, and the SLE activity (determined using the SLEDAI) were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 49 publications
(70 reference statements)
1
21
1
Order By: Relevance
“…In addition, the authors showed that CCR5∆32 genotypes are associated with development of class IV lupus nephritis [123]. Similar results were obtained by Baltus and co-workers [124] in a female Brazilian cohort. The authors investigated the association of CCR5∆32 genotypes with SLE disease susceptibility and disease activity.…”
Section: Immune System Diseasessupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, the authors showed that CCR5∆32 genotypes are associated with development of class IV lupus nephritis [123]. Similar results were obtained by Baltus and co-workers [124] in a female Brazilian cohort. The authors investigated the association of CCR5∆32 genotypes with SLE disease susceptibility and disease activity.…”
Section: Immune System Diseasessupporting
confidence: 79%
“…When the authors adjusted the results for the ethnicity of the patients, the authors showed that ethnicity influenced autoimmune responses. However, CCR5∆32 was not associated with disease activity [124]. Lupus nephritis (LN) refers to kidney inflammation and is often a result of SLE.…”
Section: Immune System Diseasesmentioning
confidence: 99%
“…The same conclusion was made by Carvalho et al [11] in Portuguese patients. In contrast, Baltus et al [14] claim that CCR5∆32 polymorphism can be considered as a risk factor in female Brazilian patients, and it is linked to the age of SLE onset. Furthermore, Mamtani et al [3] showed that CCR5 haplotype HHG*2, which contains CCR5∆32 polymorphism is connected with an elevated risk of developing systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 89%
“…However, research on the prevalence of CCR5 polymorphisms in SLE patients are ambiguous. The noticeable divergences in role of CCR5 polymorphisms in SLE patients can be explained by different methodology and methods used for testing [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation